Argentina : Selected Issues and Statistical Annex. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
The financial system in Argentina experienced substantial changes. Capital adequacy and liquidity indicators are strong in the Argentine banking industry, whereas profitability indicators are weak. The current system of mandatory health care for salaried employees is built around institutions known as obras sociales (OS). The reform addresses many problems associated with the financial system. The following statistical data are described in detail: index of agricultural production, industrial production index, price indices, automobile production, domestic demand, exports, and imports, financial assets, balance of payments, and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet